Crafting Civilization from the Mihrab: The Vital Role of Palopo’s Historic Jami’ Tua Mosque - Langaji, Abbas; Amelinda, Ria; Arifuddin, Arifuddin; Pamessangi, Andi Arif; Karim, Abdul Rahim; Hasanuddin, Muhammad Irfan (Journal of Al-Tamaddun, 2025)
When the Prophet Muhammad migrated from Mecca to Medina, the mosque not only functioned as a place of worship but also as a multifunctional center that included social, educational, economic, and political aspects. Inspired by this spirit, this study reviews the development of Islamic civilization in Palopo City, the capital of the Kingdom of Luwu, in the 17th century through the optimization of the function and role of the mosque. Particularly, it explored the factors that influenced it and the steps of fostering Islamic civilization, whose traces are still visible today. The study employed a qualitative approach with a historical research design. Data were obtained from various sources and analyzed by paying close attention to aspects of text, context, and history. This study found that the Jami’ Tua Mosque was the first building erected in 1604 when the capital of the Kingdom of Luwu was moved from Malangke to Ware in the early 17th century. The mosque was the first permanent building in the new capital city, confirming the Kingdom’s Islamic foundation of its civilization because a spiritual and social foundation was centered on the mosque. From this mosque, the kingdom’s governmental structure was reshaped, making Islam the main source of inspiration for government institutions. One of the significant changes was the addition of syara’ (Islamic law) to the four government institutions that previously consisted of ade’, wari, rapang, and bicara, making it five institutions. Based on these findings, this study recommends the Jami’ Tua Mosque of Palopo be preserved and used as an ideal example of building human civilization in the future, considering its role as the main symbol of mosque-based civilization building.